Evaluasi Ketenggangan Galur Padi Gogo terhadap Cekaman Aluminium dan Efisiensi Penggunaan Hara Kalium - Desta Wirnas; Amris Makmur; Didy Sopandie; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
A study was conducted to reevaluate 15 upland lines previously selected in a field experiment and nutrient culture experiment or tolerance to aluminum toxicity and potassium efficiency in the plastic house of Center for Crop Improvement Studies, Tajur, Bogor. The experiment was conducted in pot culture using Red Yellow Podzolic soil from Jasinga, Bogor. Two level of AI stress (no AI stress and AI stress with pH 4.8, Al saturation 80%, and exchangeable Al 16.6 mei/IOOg) and two levels of potassium fertilizer (6 kg K2Olha and 60 K2Olha) were applied. The study showed that the upland rice lines performed poorer under AI-tress condition compared to under non stress condition in plant heigl at harvest, total number of  tiller, number of productive tiller, length of spikelet and grain weight/pot. The performance of the upland rice lines was also significantly different under different level of potassium fertilizer in total number off tiller and nun1ber of productive tiller. Lines that showed significant difference in its performance under AI-stress and non stress condition were consiidered as tolerant lines. The result showed that Lalantik Bamban, Sigundil,CT65 I 0-24-3- I, Hawara Bunar, Ketombol, and Grogol were classified as AI-tolerant and K-efficient lines. Key word: Upland rice, Aluminium, Potasium